POLITICAL PARTIES AND SWING VOTERS IN THE 2014 AND 2019 ELECTIONS IN INDONESIA - Cahyani, Mauli Kurnia; Warganegara, Arizka; Maryanah, Tabah (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2022)
The failure of political parties and the mistakes of their elites have made swing voters maintained in every election. Swing voters are not the same as abstain who do not exercise their constitutional rights. Swing voters are voters who change their choice or change their support for the implementation of the previous election. This research uses descriptive qualitative research method. The results show that the swing voters are caused by the failure of political parties in carrying out the function of cadre and political education, that political parties are not a tool for the struggle of society, clarity of party programs and platforms, that pragmatic reasons are not rational, that the party's image is declining in the eyes of voters due to the behavior of political elites, the form of voter protest, mass mobilization, situational influences, candidate figures, and alternative candidates which are considered credible.